2007
DOI: 10.1086/517866
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Optical Depth in the Lyα Forest: Evidence Against Reionization atz∼6

Abstract: We examine the evolution of the IGM Ly optical depth distribution using the transmitted flux probability distribution function (PDF) in a high-resolution sample of 55 QSOs spanning absorption redshifts 1:7 < z < 5:8. The data are compared to two theoretical distributions: a model distribution based on the density distribution of MiraldaEscudé et al. (2000;MHR00) and a lognormal distribution. Assuming a spatially uniform UV background and an isothermal IGM, as was done in previous works where transmitted flux s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
302
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(330 citation statements)
references
References 55 publications
25
302
3
Order By: Relevance
“…Very recently, Giallongo et al (2015) found 22 AGN candidates at z 4 in the Candel/GOOD-S/Chandra Deep Field South field, which is suggestive of a prominent contribution of AGNs to the ionising background in the range 4 z 6.5. The resulting H I photoionisation rate is indeed consistent with various estimates at the same redshifts, based on both the flux-decrement and proximity-effect techniques (Becker et al 2007;Calverley et al 2011). …”
Section: Introductionsupporting
confidence: 84%
“…Very recently, Giallongo et al (2015) found 22 AGN candidates at z 4 in the Candel/GOOD-S/Chandra Deep Field South field, which is suggestive of a prominent contribution of AGNs to the ionising background in the range 4 z 6.5. The resulting H I photoionisation rate is indeed consistent with various estimates at the same redshifts, based on both the flux-decrement and proximity-effect techniques (Becker et al 2007;Calverley et al 2011). …”
Section: Introductionsupporting
confidence: 84%
“…Observations of the Gunn-Peterson trough in quasar spectra at z > 6 (Fan et al 2006) and transmission in the Lyα forest for z < 6 (Becker et al 2001;Djorgovski et al 2001;Fan et al 2001) suggests the epoch of reionization ends at z ∼ 6 (QHII(z ∼ 6) > 0.99). These constraints on the neutral fraction of hydrogen at the end of reionization rely on detailed modelling of both the IGM and ionizing sources making their accuracy (and therefore the exact end of reionization) the subject of debate (Becker, Rauch & Sargent 2007;Furlanetto & Mesinger 2009;Mesinger 2010;McGreer, Mesinger & Fan 2011;Robertson et al 2013). McGreer, Mesinger & Fan (2011) use the covering fraction of 'dark' pixels in quasar spectra to obtain the more conservative constraints of QHII(z = 5.5) > 0.8 and QHII(z = 6) > 0.5 on the end of reionization.…”
Section: Amdm Reionization Historymentioning
confidence: 99%
“…Several groups have made these measurements by measuring the mean transmission of QSO UV flux through the Ly forest (McDonald & Miralda-Escudé 2001;Tytler et al 2004;Bolton et al 2005;Bolton & Haehnelt 2007;Becker et al 2007), or by measuring the extent of the proximity effect (Carswell et al 1982) around high-redshift QSOs (Scott et al 2000(Scott et al , 2002. Figure 17 shows the current estimates for the total photoionization rate at high redshift, compared with our estimate of the contribution from QSOs at z $ 3:2.…”
Section: Qso Contribution To Hmentioning
confidence: 99%